SCIENTIFIC BASIS FOR THE PRODUCTION TECHNOLOGY OF FRUIT LOZENGES (marshmallow) - Mallabayev, Odiljon; Saribayeva, Dilorom (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Abstract. The article is based on the importance of enriching pastille with components useful for the human body and introducing biologically valuable substances into the receptor of this confectionery product. The technological scheme for the production of finished products is selected. The results of microbiological, sanitary and chemical analyzes of raw materials and finished products are presented. Objective. Research on the processes of preparation of confectionery products based on plant raw materials of high nutritional and biological value, expanding the range of pastila products. Results. In order to study the microbiological indicators of pastilan, test-samples were prepared in laboratory conditions. Sanitary and microbiological analysis was carried out in order to determine the shelf life of these samples. To determine the shelf life of pastilles, observations of the dynamics of microbiological indicators were carried out for 210 days, and the shelf life was set at 180 days . At the same time, the optimal conditions for its storage Pastila confectionery came to the requirements of gost 6441-2014, and the storage temperature was (18 ± 3)° C and the relative humidity of the air (no more than 75%). Conclusion. The situation in the world confectionery market shows a stable trend towards increasing production, expanding the range of products, improving the quality of raw materials, reducing its cost and increasing the consumption of confectionery products, which may indicate an increase in well-being and living standards of the population. At the expense of an herbal supplement with antioxidant properties, the biological value of the finished product increases, and an extension of the shelf life can be achieved. According to the results of the study, the eneretic value of fruit lozenges prepared on the basis of the above recipe was calculated.